Learning Obstacle pada Materi Bilangan Berpangkat pada Siswa Kelas V SD Negeri 3 Air Kumbang - Trianawati Trianawati; Nyiayu Fahriza Fuadiah; Nora Surmilasari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research was carried out with the aim of finding out the learning obstacles experienced by students, especially class V students at SD Negeri 3 Air Kumbang, using rank number material. Learning Obstacles are divided into three types, namely ontogenic obstacles, epistemological obstacles, and didactical obstacles. The research method used is a descriptive qualitative method using several instruments including the results of learning obstacle diagnostic tests, material analysis, interviews, lesson plan analysis, and analysis of textbooks used during the learning process. 20 fifth grade students at SD Negeri 3 Air Kumbang were the subjects of this research. In this research, learning obstacles were found which were divided into three categories, namely ontogenic obstacles, epistemological obstacles and didactical obstacles. Ontogenic obstacles can be seen from students' lack of enthusiasm for learning and readiness to learn. Epistemological obstacles can be seen from students' lack of understanding of a concept related to mathematics due to the limited context that students know, as well as didactical obstacles obtained from the learning tools used which can create learning obstacles during the learning process.